Nadmierne korzystanie z urządzeń mobilnych wśród dzieci - Nowak, Joanna (Studia Edukacyjne, 2018)
The article deals with the excessive use of mobile devices by children and students. The article draws attention to the earlier children’s contact with devices and public applications. The article presents the possible causes of this phenomenon and the resulting threats. The article has a theoretical and research character.